MXenes in triboelectric nanogenerators (TENGs): Present status and the future - Jiacheng Fan; Guanglei Zhang; Jia Yang; Aiguo Zhou (Journal of Advanced Ceramics, 2025)
Triboelectric nanogenerators (TENGs) represent a cutting-edge class of devices for energy conversion and self-powered sensing. The selection of appropriate triboelectric and conductive materials is critical in determining the performance of TENGs. In recent years, MXenes, particularly Ti3C2 MXenes, have emerged as promising candidates for triboelectric/conductive materials in TENGs. To elucidate the multifaceted roles of MXenes, this review examines their applications from a materials science perspective. The applications are categorized into four types based on the functional layers of TENGs where MXenes are applied: (1) MXene films as conductive layers, (2) MXene films as triboelectric layers, (3) MXene nanosheets as fillers in polymer-based triboelectric layers, and (4) MXene films as charge trapping layers. The rationale and advantages of utilizing MXenes in each application are analyzed and elucidated. Owing to their unique combination of properties, including electronegativity, electrical conductivity, and flexibility, MXenes demonstrate remarkable versatility in all functional layers, either as pure films or composite films. Systematic analysis reveals that MXene composite films are particularly promising for various applications. This review represents the first comprehensive attempt to classify MXene applications in TENGs and articulate their inherent advantages, thereby providing a foundation for the design and development of high-performance MXene-based TENGs.